Identifikasi dan Kemampuan Jamur Endofitik Asal Jagung (Zea mays L.) Terhadap Patogen Busuk Pelepah (Rhyzoctonia solani) - Shiska M Rotasouw; Johanna Taribuka; Handry R D Amanupunyo (JURNAL BUDIDAYA PERTANIAN, 2020)
Maize is a cereal crop which is an important source of food because it is the second source of carbohydrates after rice. Maize cultivation is faced with various plant diseases, that can reduce the quantity and quality of crop yield. Plant disease is one of the limiting factors for crop production and seed quality. One of the most harmful maize diseases is blight or midrib rot caused by the soil-borne fungus Rhizoctonia solani. The aim of the study was to obtain endophytic microorganisms in maize and to test the antagonistic ability of these fungi as biological control agents against R. solani. The study took place in January-September 2018 in the field and the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, University of Pattimura. Endophytic fungi isolated from maize plants from the roots, stems and leaves. Samples were cleaned in running water and air-dried. Subsequently, the samples were sterilized using 70% alcohol and immersed in sodium hypochlorite solution for 2 minutes and rinsed with sterile water 3 times. The sterilized roots, stems and leaves of maize were peeled, cut to a size of Â±5 mm, split and dried on sterile filter paper. Sterile samples were grown on PDA culture media at four points and incubated at room temperature. Visual identification was carried out with the aid of a microscope on fungi growing on the culture media. The results showed the presence of the endophytic fungi Trichoderma sp., Aspergillus sp., Penicillium sp., Diplodia sp. and Mucor sp. These fungal species showed different inhibitory powers, which included mechanisms for direct parasitizing of pathogens, producing antibiotics and competition for space and nutrients. Keywords: antagonism, corn, endophytic fungi, identification, pathogenic fungus, Rhizoctonia solani ABSTRAK Jagung (Zea mays L.) merupakan tanaman serelia yang termasuk bahan pangan penting karena merupakan sumber karbohidrat kedua setelah beras. Salah satu kendala dalam budidaya tanama jagung adalah penurunan produksi akibat serangan patogen penyebab penyakit. Untuk menekan perkembangan penyakit dilakukan pengendalian dengan menggunakan mikroorganisme endofitik asal akar, batang dan daun jagung sebagai agensia pengendalian hayati. Penelitian ini bertujuan mengisolasi dan mengidentifikasi mikroorganisme endofitik asal jagung secara morfologi, mendapatkan mikroorganisme endofitik yang memiliki kemampuan antagonis terhadap jamur Rhizoctonia solani penyebab penyakit busuk pelepah pada jagung. Penelitian berlangsung dalam 2 tahap, yaitu di lapangan dan di Laboratorium Hama dan Penyakit Tumbuhan Fakultas Pertanian, Universitas Pattimura. Sampel tanaman diperoleh dari beberapa kebun petani di wilayah Kota Ambon. Hasil penelitian yang diperoleh adalah bahwa jamur endofitik Trichoderma sp, Aspergillus sp, Penicillium sp, Diplodia sp dan Mucor sp. memiliki daya penghambatan yang berbeda-beda, yaitu 78.57% (Trichoderma sp), 65.86% (Penicillium sp), 43.29% (Aspergillus sp), 36.71 (Diplodia sp) dan 34.44% (Mucor sp). Kata kunci: antagonisme, identifikasi, jagung, jamur endofitik, jamurpatogenik, Rhizoctonia solani